1989
DOI: 10.1177/101053958900300411
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Among Medical Students in Hong Kong

Abstract: A survey was conducted among two classes of medical students (N = 293) at the University of Hong Kong to study their smoking habits and knowledge of and attitudes toward smoking. The response rate was 97.3%. There was only one daily smoker (0.4%) and 21 occasional smokers (7.4%). While the respondents regarded health and self-discipline as the main reasons for not smoking, the social taboo against smoking among young people might have also deterred this educated elite from smoking. Many of them failed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Although there are only three questions measuring the attitude on tobacco control, we believe that the result can still reflect the attitude on tobacco control as these questions measure the more controversial and important issues regarding the students' opinion and behaviour on tobacco control in Hong Kong. In a past survey on medical students in Hong Kong (Cheng, Lam & Ratanasiri 1989), 69% of final year and 57% of first year students strongly or somewhat agreed that tobacco advertising should be completely banned. The corresponding figure for young doctors was 65% (Cheng & Lam 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are only three questions measuring the attitude on tobacco control, we believe that the result can still reflect the attitude on tobacco control as these questions measure the more controversial and important issues regarding the students' opinion and behaviour on tobacco control in Hong Kong. In a past survey on medical students in Hong Kong (Cheng, Lam & Ratanasiri 1989), 69% of final year and 57% of first year students strongly or somewhat agreed that tobacco advertising should be completely banned. The corresponding figure for young doctors was 65% (Cheng & Lam 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Both overseas and local medical students lack the relevant knowledge about cigarette smoking, especially the harmful effects to health (Cheng, Lam & Ratanasiri 1989; Crofton, Fréour & Tessier 1994). Young doctors also have inadequate knowledge and skill (Cheng & Lam 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illicit drug use rates of < 0.5% among Chinese youth (aged under 21 years) have been reported. Several other studies have also reported substance use behavior in the Hong Kong and mainland Chinese population 10–12 . Among secondary school children in Hong Kong 10 and mainland China, 11 ever smoking rates of 2 % and 20% have been reported.…”
mentioning
confidence: 93%
“…However, quitting smoking turned out to be anything but simple, reason for which more and more researchers of this process consider it a complex learning process in its essence, (O'Connell et al, 2004;Endo et al, 2009;Lee, Catley, & Harris, 2012). Moreover, it is worth noting that, whereas at the beginning, researches on teenager samples prevailed, lately more attention has been given to researching this phenomenon within university space, (Cheng, Lam, & Ratanasiri, 1989;Field, Rush, Cole, & Goudie, 2007;Hsia & Spruijt-Metz, 2008;Araújo, Loukas, & Gottlieb;Lochbuehler, Voogd, Scholte, & Engels, 2011). The university student seems to be the ideal subject because, unlike the teenagers, he has already overcome the period of cognitive immaturity and emotional imbalance.…”
Section: General Aspectsmentioning
confidence: 95%